Right of the court to obtain information covered by banking secrecy in cases for reserved portion (part 2) - Łukańko, Bernard (Studia Iuridica Toruniensia, 2023)
The study analyses the possibility of qualifying a case for reserved portion as “succession proceedings” within the meaning of the provisions on banking secrecy laid down in the Banking Act 1997 and the resulting obligation of the bank to provide the court with information covered by secrecy in civil proceedings. The author of the study analysed both the views of the case law and legal doctrine relating to banking secrecy and considered the arguments both in favour of the principle of maximal extension of the bank secrecy and referral to succession proceedings within the meaning of Article 627 et seq. of the Code of Civil Procedure ruling out an extensive interpretation of the exceptions, as well as the opposite opinions. Moreover, the analysis covered legislative reasons for the introduction of the exception in Article 105 section 1 subsection 2(d) of the Banking Act. Essential values, including those of a constitutional nature, supporting the effectiveness of a claim for reserved portion determined the need for the aforementioned provision of the Banking Act to also cover cases for reserved portion.